Analysis of higher purity copper cathode Cu-CATH-1. Method for determination of cadmium, manganese and silver (screening procedure for chromium, cobalt, iron, nickel and zinc) by atomic absorption spectrophotometry Part 1, (30th September 1987) - British Standards Institution,
No abstract available